Midgut neuroendocrine tumour presenting as orbital metastases. Issue 2 (3rd May 2020) - Hoenck, Helen; Conradie, Wilhelmina; Conradie, Magda; Coetzee, Ankia
Abstract : Metastasis of a neuroendocrine tumour (NET) to the orbit is a rare occurrence, with published data limited to a few case reports. Orbital involvement usually presents with proptosis and decreased ocular mobility. Timing, in relation to the presentation of the primary tumour (PT), varies. The authors report a case of a 58-year-old female whose clinical presentation of orbital metastases preceded clinical suspicion of a midgut NET. Her presentation was with severe headaches and bilateral ptosis, histologically proven to be due to orbital muscle infiltration. The PT location was determined from the histopathological markers on orbital muscle biopsy, which suggested a gastrointestinal origin. Abdominal computed tomography (CT) was in keeping with a midgut NET with features characteristic of a desmoplastic reaction. Additional CT findings were widespread metastases, corroborated by nuclear imaging. The patient developed carcinoid syndrome and subsequently underwent surgical resection of the PT due to acute bowel obstruction. Her carcinoid symptoms and ocular findings improved on continued somatostatin receptor analogue therapy, but she sadly died within one month following surgery.